Assessing the Use of Digital Communication Technologies by Select Federal Parastatals During the 2020 Covid-19 Era - Blessing, Salifu; Igyuve, Anthony I.; Rabiu, M. S. (ALSYSTECH Journal of Education Technology, 2025)
The Covid-19 pandemic fundamentally transformed modes of communication by shifting reliance toward digital communication technologies (DCTs) in response to physical distancing measures. Against this backdrop, this study examined the adoption and use of DCTs in selected federal parastatals in Nigeria during the Covid-19 era, with a particular focus on benefits, challenges, and implications for work, education, and mental health. A survey research design was employed, and data were collected through questionnaires administered to staff of the National Productivity Centre (NPC) and the Nigeria Centre for Disease Control (NCDC) in Abuja. The findings reveal a high level of DCT adoption within both organizations, particularly for virtual meetings, which served as supportive tools in mitigating the disruptive effects of the pandemic. However, challenges such as limited digital literacy among civil servants, unequal access to reliable online services, and the overwhelming proliferation of online information were found to exacerbate anxiety, social tensions, and discriminatory behaviors. The study concludes that bridging the digital divide is critical, recommending that policymakers prioritize affordable access to DCTs, while organizations should invest in upgrading digital infrastructure and skills, benchmarking against high-performing institutions to enhance competitiveness. By illuminating the dual role of DCTs as both enablers and potential stressors, this study underscores their long-term significance in shaping organizational resilience and social interaction in a post-pandemic future.